Two-dimensional hydrodynamic modelling of channel processes and floods characteristics at the confluence of the Amur and Zeya rivers - E. Fingert; E. Fingert; I. Krylenko; I. Krylenko; V. Belikov; P. Golovlyov; A. Zavadskii; M. Samokhin (Proceedings of the International Association of Hydrological Sciences, 2019)
Two-dimensional hydrodynamic STREAM_2D model have been applied to the confluence of Amur and Zeya rivers. Main flow characteristics and possible channel changes are considered during modeling for two scenarios – without dams near Big Heihe Island (1) and with four dams in the side channels around the island (2). Results of modeling demonstrate impact of dams construction on flow concentrating in the main channel, which can lead to increasing of flow velocities and subsequent erosion in main Amur River channel downstream the river confluence.